2020
DOI: 10.4025/actascianimsci.v42i1.47380
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of reproductive characteristics in Iran-Black sheep

Abstract: This study was conducted to estimate genetic parameters and trends for reproduction traits using data collected at the breeding station of Iran-Black sheep during 1980 to 2004. The traits included in the analyses were litter size at birth (LSB) and weaning (LSW) and litter mean weight per lamb born (LMWLB) and weaned (LMWLW) as basic traits, and total litter weight at birth (TLWB) and weaning (TLWW) as composite traits. Direct heritability estimates for LSB, TLWB, LMWLB, LSW, TLWW and LMWLW were 0.11, 0.07, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
3
2
1
Order By: Relevance
“…Genetic and environmental factors influence birth weight characteristics of Sapudi lambs; permanent factors constitute 10.8%, while temporary environmental factors constitute 89.2%. The repeatability value of birth weight obtained from the results of this study is almost the same (low category) when compared to that reported in lambs, namely 0.118 (Piwczyński et al, 2011), 0.13 (Ozturk et al, 2018), and 0, 19 (Yafarivard et al, 2015 but lower than the Iranian lamb of 0.27 including the medium category (Baneh et al, 2019).…”
Section: Estimated Repeatability Of Birth Weight and Weaning Weightsupporting
confidence: 83%
“…Genetic and environmental factors influence birth weight characteristics of Sapudi lambs; permanent factors constitute 10.8%, while temporary environmental factors constitute 89.2%. The repeatability value of birth weight obtained from the results of this study is almost the same (low category) when compared to that reported in lambs, namely 0.118 (Piwczyński et al, 2011), 0.13 (Ozturk et al, 2018), and 0, 19 (Yafarivard et al, 2015 but lower than the Iranian lamb of 0.27 including the medium category (Baneh et al, 2019).…”
Section: Estimated Repeatability Of Birth Weight and Weaning Weightsupporting
confidence: 83%
“…Also [43] reported that the fertility rate was lower in 1.5-year-old ewes than in older ewes. Same results were obtained by [45] reported that decreasing reproductive performance after approximately five parities can be explained by an increase in twinning rate and conception rate with age.…”
Section: Effect Of Supplementation Strategies and Parity Order On Rep...supporting
confidence: 82%
“…[30] reported a greater effect of ewe live weight on reproductive performance in younger ewes than older ewes. Also [43][44][45][46][47][48][49][50][51][52][53][54][55][56], who showed that litter size was more in the protein supplement group than the control group (no supplements of protein). Increasing the pre mating weight ewes could increase the pregnancy rate and multiple births [10,11,39].…”
Section: Effect Of Supplementation Strategies and Parity Order On Lit...mentioning
confidence: 99%
“…In addition, genes that increase TLWB may also increase the mother's milk and mothering abilities, since the lamb's weaning weight depends on the ewe's maternal ability besides its genotype. The r p values ranged from − 0.19 for LSB-LMWLW to 0.66 for LSB-LSW, and these ndings are according to previous studies(Mohammadi et al, 2013;Eteqadi et al, 2017;Baneh et al, 2020). Some of the studied reproductive traits show a medium and positive phenotypic correlation, suggesting that environmental factors that enhance one trait may also positively impact other traits.…”
supporting
confidence: 84%
“…, and Iran-Black(Baneh et al, 2020) sheep populations. Our analysis indicates that the estimated service sire effect ranges from 0.012 to 0.039, as reported by scholarly sources(Mohammadi et al, 2015;Amiri Roudbar et al, 2018).…”
mentioning
confidence: 99%